Non-aqueous electrolyte secondary battery

The integration of silicon-containing materials, carbonaceous materials, and a specific amount of carbon nanotubes in the negative electrode mixture, combined with a cyclic ester-containing nonaqueous electrolyte, addresses the challenges of volume changes and side reactions in nonaqueous electrolyte secondary batteries, resulting in improved cycle characteristics and reduced electrolyte consumption.

JP7664532B2Active Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022512058
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-25
Publication Date
2025-04-18
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

Nonaqueous electrolyte secondary batteries using silicon-containing materials as negative electrode active materials face challenges due to large volume changes during lithium ion absorption and release, leading to conductive path disruptions and reduced cycle characteristics. Additionally, the use of carbon nanotubes increases side reactions and nonaqueous electrolyte consumption.

Method used

A nonaqueous electrolyte secondary battery configuration that includes a negative electrode mixture with a silicon-containing material, a carbonaceous material, and a specific amount of carbon nanotubes (0.005% to 0.05% by mass), along with a nonaqueous electrolyte containing at least one cyclic ester (cyclic sulfate, cyclic sulfite, or sultone).

Benefits of technology

This configuration effectively suppresses the reduction of the nonaqueous electrolyte during repeated charging and discharging, maintains high cycle characteristics, and reduces side reactions, thereby enhancing the battery's overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664532000002
    Figure 0007664532000002
  • Figure 0007664532000001
    Figure 0007664532000001
Patent Text Reader

Abstract

A nonaqueous electrolyte secondary battery is provided with a positive electrode, a negative electrode and a nonaqueous electrolyte. The negative electrode contains a negative-electrode mixture including a negative-electrode active material that can electrochemically store and discharge lithium ions, and a carbon nanotube. The negative-electrode active material contains a silicon-containing material and a carbonaceous material. The nonaqueous electrolyte contains at least one cyclic ester selected from the group consisting of a cyclic sulfate, a cyclic sulfite, and a sultone. The content of the carbon nanotube in the negative-electrode mixture is 0.005-0.05 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] A non-aqueous electrolyte secondary battery, typified by a lithium ion secondary battery, comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. A non-aqueous electrolyte solution is mainly used as the non-aqueous electrolyte. The negative electrode comprises a negative electrode mixture containing a negative electrode active material capable of electrochemically absorbing and releasing lithium ions. A material capable of electrochemically absorbing and releasing lithium ions is used as the negative electrode active material. Examples of such materials include carbonaceous materials and silicon-containing materials. In addition, a carbonaceous material that does not absorb and release lithium ions, such as carbon fibers and carbon nanotubes, may be added to the negative electrode mixture.

[0003] Patent Document 1 proposes the use of a composite electrode agent in a lithium ion secondary battery, the composite electrode agent including particles containing an element capable of absorbing and desorbing lithium ions, carbon particles capable of absorbing and desorbing lithium ions, multi-walled carbon tubes, and carbon nanofibers.

[0004] Patent Document 2 proposes using an electrode produced by dry-mixing an active material, carbon fibers having a fiber diameter of 50 nm or more and 300 nm or less, carbon fibers having a fiber diameter of 5 nm or more and 400 nm or less, carbon black, and a binder to obtain a mixture, adding a liquid medium to this mixture and kneading it, and forming the kneaded product into a sheet shape, in a lithium-ion battery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-146519 A [Patent Document 2] JP 2014-160590 A Summary of the Invention

[0006] Silicon-containing materials undergo large volume changes due to the absorption and release of lithium ions. Therefore, when silicon-containing materials are used as negative electrode active materials, the conductive paths between the negative electrode active material particles are cut, and the negative electrode active material particles are easily isolated, and cycle characteristics are easily deteriorated. When a negative electrode active material containing a silicon-containing material is used, the combination of carbon nanotubes makes it easier to ensure conductivity between the negative electrode active material particles. On the other hand, the use of carbon nanotubes increases the surface area of ​​the negative electrode mixture, increasing side reactions and causing significant consumption of non-aqueous electrolyte.

[0007] One aspect of the present disclosure is a battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, the negative electrode comprises a negative electrode mixture including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions and carbon nanotubes; the negative electrode active material includes a silicon-containing material and a carbonaceous material, the non-aqueous electrolyte contains at least one cyclic ester selected from the group consisting of a cyclic sulfate ester, a cyclic sulfite ester, and a sultone, The present invention relates to a nonaqueous electrolyte secondary battery, wherein the content of the carbon nanotubes in the negative electrode mixture is 0.005% by mass or more and 0.05% by mass or less.

[0008] This makes it possible to suppress the reduction in the non-aqueous electrolyte when the non-aqueous electrolyte secondary battery is repeatedly charged and discharged. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In non-aqueous electrolyte secondary batteries, silicon-containing materials used as negative electrode active materials have a high capacity, but the volume change associated with the absorption and release of lithium ions during charging and discharging is large. Therefore, in a negative electrode mixture containing a silicon-containing material, the conductive path between the negative electrode active material particles is cut, and the negative electrode active material particles are easily isolated. As a result, cycle characteristics are deteriorated. If carbon nanotubes are further contained in such a negative electrode mixture, the carbon nanotubes are interposed between the negative electrode active material particles, suppressing the disconnection of the conductive path, and relatively high cycle characteristics can be ensured. However, when the negative electrode mixture contains carbon nanotubes, the surface area of ​​the negative electrode mixture increases, and side reactions increase, resulting in a significant decrease in the non-aqueous electrolyte after repeated charging and discharging.

[0011] Cyclic esters such as ethylene sulfite and propane sultone hardly contribute to suppressing the decrease in the non-aqueous electrolyte after repeated charging and discharging, even when the non-aqueous electrolyte containing such a cyclic ester is combined with a negative electrode mixture containing no carbon nanotubes. However, it has been revealed that, unexpectedly, when the non-aqueous electrolyte containing the above-mentioned cyclic ester is combined with a negative electrode mixture containing a specific amount of carbon nanotubes, the decrease in the non-aqueous electrolyte after repeated charging and discharging is suppressed.

[0012] In view of the above, the nonaqueous electrolyte secondary battery of the present disclosure includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The negative electrode includes a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, and a negative electrode mixture including carbon nanotubes. The negative electrode active material includes a silicon-containing material and a carbonaceous material. The nonaqueous electrolyte includes at least one cyclic ester selected from the group consisting of cyclic sulfate esters, cyclic sulfite esters, and sultones. The content of the carbon nanotubes in the negative electrode mixture is 0.005% by mass or more and 0.05% by mass or less. Hereinafter, the silicon-containing material may be referred to as a Si-containing material, and the carbon nanotubes may be referred to as CNTs. The cyclic ester may be simply referred to as a first component.

[0013] With this configuration, the nonaqueous electrolyte secondary battery of the present disclosure can suppress the decrease in nonaqueous electrolyte after repeated charging and discharging as described above, even though it uses CNT. The reason why the decrease in nonaqueous electrolyte is suppressed is unclear, but it is believed that the first component acts on the CNT to suppress side reactions in which the CNT directly or indirectly participates, since the effect of suppressing the decrease in nonaqueous electrolyte is not observed when the negative electrode mixture does not contain CNT even if the first component is used in the nonaqueous electrolyte. By using the first component, a sufficient effect of suppressing the decrease in nonaqueous electrolyte can be obtained to compensate for the decrease in nonaqueous electrolyte caused by the use of CNT.

[0014] In the nonaqueous electrolyte secondary battery of the present disclosure, the use of the first component suppresses side reactions in the negative electrode, so that electrons are preferentially consumed in the charge / discharge reaction. Therefore, the capacity decrease at the beginning of charge / discharge can be suppressed. In addition, since the negative electrode mixture contains CNTs, disconnection of the conductive path in the negative electrode mixture during repeated charge / discharge is suppressed, even though a Si-containing material is used as the negative electrode active material. In addition, the first component suppresses side reactions even during repeated charge / discharge, so that the capacity decrease after repeated charge / discharge can be suppressed. Therefore, excellent cycle characteristics can be ensured.

[0015] In addition, when the content of CNT in the negative electrode mixture is less than 0.005% by mass, the decrease in the non-aqueous electrolyte is not evident even if the CNT is used in the negative electrode mixture. Even if a negative electrode mixture containing CNT at such a content is combined with a non-aqueous electrolyte containing the first component, the effect of suppressing the decrease in the non-aqueous electrolyte by the first component is hardly exhibited. On the other hand, even if a negative electrode mixture containing CNT more than 0.05% by mass is combined with a non-aqueous electrolyte containing the first component, the effect of suppressing the decrease in the non-aqueous electrolyte by the first component is small. In a conventional non-aqueous electrolyte secondary battery, when CNT is used in the negative electrode mixture, as shown in Patent Documents 1 and 2, the content of CNT in the negative electrode mixture is 0.1% by mass or more and about 9% by mass. In such a conventional non-aqueous electrolyte secondary battery, the consumption of the non-aqueous electrolyte due to the use of CNT is significant even if a non-aqueous electrolyte containing the first component is used, and the effect of suppressing the decrease in the non-aqueous electrolyte by the first component is hardly obtained, or is small even if it is obtained.

[0016] Each component of the nonaqueous electrolyte secondary battery according to the present disclosure will be described in more detail below.

[0017] (Negative electrode) The negative electrode includes a negative electrode mixture. The negative electrode may include a negative electrode mixture and a negative electrode current collector that holds the negative electrode mixture. The negative electrode usually includes a layered negative electrode mixture (hereinafter referred to as a negative electrode mixture layer). The negative electrode mixture includes a negative electrode active material and CNT. The negative electrode mixture may further include at least one selected from the group consisting of a binder, a thickener, and a conductive agent other than CNT.

[0018] (Negative electrode active material) As the negative electrode active material, a material capable of electrochemically absorbing and releasing lithium ions is used. The negative electrode active material includes a Si-containing material and a carbonaceous material. The carbonaceous material expands and contracts less during charging and discharging than the Si-containing material. By using the Si-containing material and the carbonaceous material in combination, the contact state between the negative electrode active material particles and between the negative electrode mixture and the negative electrode current collector can be better maintained during repeated charging and discharging. Therefore, by combining the carbonaceous material with the Si-containing material, it is easy to ensure high cycle characteristics while ensuring the high capacity of the Si-containing material. The negative electrode active material may contain other negative electrode active materials other than the Si-containing material and the carbonaceous material as necessary. Examples of the other negative electrode active materials include at least one selected from the group consisting of Sn alone, Sn alloys, and Sn compounds such as Sn oxides.

[0019] (Si-containing material) Examples of silicon-containing materials include silicon itself, silicon alloys, silicon compounds (such as silicon oxides), and composite materials in which silicon particles (fine Si phases) are dispersed in a lithium ion conductive phase (matrix). Examples of silicon oxides include SiO x For example, x may be 0.5≦x<2, or 0.8≦x≦1.6.

[0020] From the viewpoint of ensuring higher cycle characteristics, it is preferable that the Si-containing material contains the above composite material. The lithium ion conductive phase is SiO 2 It is preferable that the lithium ion conductive phase contains at least one selected from the group consisting of a SiO phase and a silicate phase. The lithium ion conductive phase may further contain a carbon phase. The lithium ion conductive phase may form an amorphous phase. The Si-containing material is preferably a SiO 2 These may include composite materials having silicon particles dispersed within a phase, composite materials having silicon particles dispersed within a silicate phase, composite materials having silicon particles dispersed within a carbon phase, and the like.

[0021] SiO 2 The SiO phase is an amorphous phase containing 95% or more by weight of silicon dioxide. 2 Composites with silicon particles dispersed in the phase are SiO x where x may be, for example, in the ranges given above. x For example, silicon monoxide is heat-treated to produce SiO 2 The SiO phase and the fine Si phase are separated using a transmission electron microscope (TEM). x When observing the cross section of a particle, SiO 2 Silicon particles can be seen dispersed within the phase.

[0022] The silicate phase preferably contains at least one of an alkali metal element (a Group 1 element other than hydrogen in the long-form periodic table) and a Group 2 element in the long-form periodic table. The alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. The Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The lithium silicate phase has the formula: Li 2y SiO 2+yIt may have a composition represented by (0 < y < 2). y may be 1 / 2 or may be 1. A composite material in which silicon particles are dispersed in a silicate phase can be obtained, for example, by pulverizing and atomizing a mixture of a silicate and raw material silicon while stirring with a ball mill or the like, and then heat-treating the mixture in an inert atmosphere.

[0023] The content of silicon particles dispersed in the silicate phase may be 30% by mass or more and 95% by mass or less, or may be 35% by mass or more and 75% by mass or less with respect to the whole composite material.

[0024] The carbon phase contains, for example, poorly crystalline amorphous carbon. The amorphous carbon may be, for example, easily graphitizable carbon (hard carbon) or hardly graphitizable carbon (soft carbon). A composite material in which silicon particles are dispersed in the carbon phase can be obtained, for example, by pulverizing and atomizing a mixture of a carbon source and raw material silicon while stirring with a ball mill or the like, and then heat-treating the mixture in an inert atmosphere. As the carbon source, for example, saccharides such as carboxymethyl cellulose (CMC) and water-soluble resins such as polyvinylpyrrolidone are used.

[0025] The composition of the Si-containing material is determined, for example, by obtaining a backscattered electron image of the cross section of the negative electrode active material layer with a field emission scanning electron microscope (FE-SEM), observing the particles of the Si-containing material, and performing elemental analysis on the observed particles of the Si-containing material. For elemental analysis, for example, electron probe micro analyzer (EPMA) analysis or the like is used. The composition of the lithium ion conduction phase can also be determined by the above analysis.

[0026] The Si-containing material may be used alone or in combination of two or more.

[0027] The Si-containing material is, for example, a particulate material. The average particle size (D50) of the Si-containing material is, for example, 1 μm or more and 25 μm or less, and preferably 4 μm or more and 15 μm or less. In the above range, good battery performance is easily obtained.

[0028] In this specification, the average particle size (D50) means the particle size (volume average particle size) at which the volume cumulative value is 50% in the particle size distribution measured by the laser diffraction scattering method. For example, the "LA-750" manufactured by HORIBA Co., Ltd. can be used as the measuring device.

[0029] From the viewpoint of improving the electrical conductivity, at least a part of the particle surface of the Si-containing material may be coated with a conductive layer. The conductive layer contains a conductive material such as conductive carbon. The amount of the conductive layer is, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the total of the Si-containing material particles and the conductive layer. The Si-containing material particles having a conductive layer on the surface can be obtained, for example, by mixing coal pitch or the like with the Si-containing material particles and heat-treating the mixture in an inert atmosphere.

[0030] The Si-containing material undergoes a large volume change due to expansion and contraction during charging and discharging. Therefore, when the ratio of the Si-containing material in the negative electrode active material increases, the cycle characteristics tend to decrease. According to the present disclosure, since the negative electrode mixture contains a specific amount of CNT, even when the ratio of the Si-containing material in the negative electrode active material is relatively high, disconnection of the conductive path is suppressed, and high cycle characteristics are easily ensured. The ratio of the Si-containing material in the negative electrode active material is preferably 4% by mass or more, and may be 5% by mass or more. The ratio of the Si-containing material is preferably 15% by mass or less, and may be 10% by mass or less. These lower and upper limits can be combined arbitrarily.

[0031] (carbonaceous material) Examples of the carbonaceous material include graphite, easily graphitized carbon (soft carbon), and non-graphitizable carbon (hard carbon). The carbonaceous material may be used alone or in combination of two or more.

[0032] Among them, graphite is preferable as the carbonaceous material because it has excellent charge / discharge stability and small irreversible capacity. Examples of graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles. The graphite particles may partially contain amorphous carbon, graphitizable carbon, and non-graphitizable carbon.

[0033] Graphite is a carbonaceous material with a developed graphite crystal structure. The interplanar spacing d002 of the (002) plane of graphite measured by X-ray diffraction may be, for example, 0.340 nm or less, or 0.3354 nm or more and 0.340 nm or less. The crystallite size Lc(002) of graphite may be, for example, 5 nm or more, or 5 nm or more and 200 nm or less. The crystallite size Lc(002) is measured, for example, by the Scherrer method. When the interplanar spacing d002 of the (002) plane of graphite and the crystallite size Lc(002) are within the above ranges, a high capacity is easily obtained.

[0034] The ratio of the carbonaceous material in the negative electrode active material is, for example, 97% by mass or less, may be 96% by mass or less, or may be 95% by mass or less. The ratio of the carbonaceous material in the negative electrode active material is, for example, 76% by mass or more, may be 80% by mass or more, 85% by mass or more, or may be 90% by mass or more. These lower and upper limits can be combined in any desired manner.

[0035] The total amount of the Si-containing material and the carbonaceous material in the negative electrode active material is preferably 90% by mass or more, and may be 95% by mass or more or 98% by mass or more. The total amount of the Si-containing material and the carbonaceous material in the negative electrode active material is 100% by mass or less. The negative electrode active material may be composed of only the Si-containing material and the carbonaceous material.

[0036] (CNT) CNTs are carbonaceous materials with nanometer diameters that have a structure in which a sheet (graphene) of a six-membered ring network formed by carbon atoms is rolled into a cylindrical shape. CNTs have excellent electrical conductivity. When the number of graphene layers that make up the cylindrical structure is one, it is called a single-walled CNT (SWCNT: single-walled carbon nanotube). When the number of layers is multiple, it is called a multi-walled CNT (MWCNT: multi-walled carbon nanotube).

[0037] The CNTs preferably include SWCNTs, which not only makes it easier to ensure higher cycle characteristics but also makes it easier for the first component to exert its effect of suppressing the decrease in the non-aqueous electrolyte.

[0038] The proportion of SWCNTs in the CNTs is, for example, 50% or more, or may be 75% or more, or may be 90% or more, and the proportion of SWCNTs in the CNTs is 100% or less.

[0039] The proportion of SWCNTs in the CNTs is the ratio of the number of SWCNTs to the total number of CNTs.

[0040] The presence of CNTs in the negative electrode mixture can be confirmed, for example, by an image of a cross section of the negative electrode mixture layer taken with a scanning electron microscope (SEM).

[0041] The proportion of SWCNTs in the CNTs contained in the negative electrode mixture is determined by the following method.

[0042] An image of the cross section of the negative electrode mixture layer or CNTs is obtained using an SEM. In the SEM image, a number of CNTs (e.g., 50 to 200) are randomly selected and observed, the number of SWCNTs is counted, and the ratio of the number of SWCNTs to the total number of selected CNTs is calculated.

[0043] The content of CNT in the negative electrode mixture is 0.005% by mass or more, and may be 0.01% by mass or more, or 0.015% by mass or more, or may be 0.02% by mass or more. When the content of CNT is in such a range, higher cycle characteristics can be ensured, and the effect of suppressing the decrease of the nonaqueous electrolyte by using a nonaqueous electrolyte containing the first component is more likely to be manifested. The content of CNT is 0.05% by mass or less, and may be 0.03% by mass or less. When the content of CNT is in such a range, the decrease of the nonaqueous electrolyte can be further suppressed by using a nonaqueous electrolyte containing the first component. These lower limit values ​​and upper limit values ​​can be combined arbitrarily.

[0044] Quantitative analysis of CNTs is performed, for example, by combining Raman spectroscopy and thermogravimetric analysis.

[0045] From the standpoint of reducing disconnection of the conductive path during charging and discharging, the average diameter of the CNTs may be, for example, 1 nm or more and 10 nm or less, or 1 nm or more and 5 nm or less.

[0046] From the viewpoint of reducing disconnection of the conductive paths during charge and discharge, the average length of the CNTs may be, for example, 1 μm or more and 100 μm or less, or 5 μm or more and 20 μm or less.

[0047] The average length and average diameter of the CNTs can be obtained from an image of the cross section of the negative electrode mixture layer or the CNTs using at least one of SEM and TEM. More specifically, in the captured image, a number of CNTs (e.g., 50 to 200) are arbitrarily selected, their lengths and diameters are measured, and the averages are calculated to obtain the average length and average diameter. The length of the CNTs means the length of the CNTs when they are stretched linearly.

[0048] (others) As the binder, for example, a resin material is used. As the binder, for example, fluororesin (for example, polytetrafluoroethylene, polyvinylidene fluoride), polyolefin resin (for example, polyethylene, polypropylene), polyamide resin (for example, aramid resin), polyimide resin (for example, polyimide, polyamideimide), acrylic resin (for example, polyacrylic acid, polymethacrylic acid, acrylic acid-methacrylic acid copolymer, ethylene-acrylic acid copolymer, or salts thereof), vinyl resin (for example, polyvinyl acetate), rubber-like material (for example, styrene-butadiene copolymer rubber (SBR)) can be mentioned. As the binder, one kind may be used alone, or two or more kinds may be used in combination.

[0049] Examples of thickeners include cellulose derivatives such as cellulose ether. Examples of cellulose derivatives include CMC and its modified products, methylcellulose, and the like. Modified CMC also includes salts of CMC. Examples of salts include alkali metal salts (e.g., sodium salts), ammonium salts, and the like. The thickeners may be used alone or in combination of two or more.

[0050] Examples of conductive agents other than CNT include conductive fibers and conductive particles other than CNT. Examples of conductive fibers include carbon fibers and metal fibers. Examples of conductive particles include conductive carbon (carbon black, etc.) and metal powder. The conductive agents may be used alone or in combination of two or more.

[0051] The negative electrode current collector is selected according to the type of the nonaqueous electrolyte secondary battery. For example, a sheet-shaped negative electrode current collector may be used. For example, a metal foil may be used as the current collector. In addition, a porous current collector may be used. For example, a mesh-shaped current collector, a punched sheet, and an expanded metal may be used as the current collector.

[0052] Examples of the material for the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, and copper alloy.

[0053] The thickness of the negative electrode current collector is not particularly limited, but may be, for example, 1 to 50 μm, and may be 5 to 30 μm.

[0054] The negative electrode can be formed, for example, by applying a negative electrode slurry, in which the components of the negative electrode mixture are dispersed in a dispersion medium, to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface or both surfaces of the sheet-shaped negative electrode current collector.

[0055] The dispersion medium is not particularly limited, but examples thereof include water, alcohol (eg, ethanol), ether (eg, tetrahydrofuran), amide (eg, dimethylformamide), N-methyl-2-pyrrolidone (NMP), or a mixed solvent thereof.

[0056] (positive electrode) The positive electrode may include a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as optional components. The dispersion medium can be selected from, for example, those exemplified for the negative electrode.

[0057] As the positive electrode active material, for example, a composite oxide containing lithium and a transition metal is used. Examples of the transition metal include Ni, Co, and Mn. Examples of the composite oxide containing lithium and a transition metal include Li a Chief of Staff 2 , Li a NiO 2 , Li a MnO 2 , Li a Co b1 Ni 1-b1 O 2 , Li a Cob1 M 1-b1 O c1 、 Li a Ni 1-b1 M b1 O c1 、 Li a Mn 2 O 4 、 Li a Mn 2-b1 M b1 O 4 include. Here, a = 0 to 1.2, b1 = 0 to 0.9, c1 = 2.0 to 2.3. M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. The a value indicating the molar ratio of lithium increases or decreases by charge and discharge.

[0058] Among them, Li a Ni b2 M 1-b2 O 2 (0 < a ≤ 1.2, 0.3 ≤ b2 ≤ 1, and M is at least one selected from the group consisting of Mn, Co, and Al.) The lithium nickel composite oxide represented is preferred. From the viewpoint of increasing the capacity, it is more preferable to satisfy 0.85 ≤ b2 ≤ 1. From the viewpoint of the stability of the crystal structure, Li a Ni b2 Co c2 Al d O 2 (0 < a ≤ 1.2, 0.85 ≤ b2 < 1, 0 < c2 ≤ 0.15, 0 < d ≤ 0.1, b2 + c2 + d = 1) is even more preferable.

[0059] As the binder, the resin materials exemplified for the negative electrode can be used. As the conductive agent, for example, those exemplified for the negative electrode can be selected. Graphite may be used as the conductive agent.

[0060] The shape and thickness of the positive electrode current collector can be selected from the shapes and ranges described for the negative electrode current collector, respectively. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0061] (Non-aqueous electrolyte) A liquid nonaqueous electrolyte is usually used as the nonaqueous electrolyte. The nonaqueous electrolyte usually contains a nonaqueous solvent and a lithium salt dissolved in the nonaqueous solvent, and further contains a first component.

[0062] (1st component) As the first component, at least one selected from the group consisting of cyclic sulfate ester, cyclic sulfite ester, and sultone is used. The first component contains at least -S(=O) 2 It may contain -O- or -S(=O)-O- as a unit constituting a ring.

[0063] Examples of the cyclic sulfate include alkylene sulfate and alkenylene sulfate. 2-4 Alkylene sulfate, C 2-4 Alkenylene sulfates may also be used. Specific examples of cyclic sulfates include ethylene sulfate, propylene sulfate, trimethylene sulfate, butylene sulfate, and vinylene sulfate.

[0064] Examples of cyclic sulfites include alkylene sulfites and alkenylene sulfites. 2-4 Alkylene sulfite, C 2-4 Alkenylene sulfite, etc. may also be used. Specific examples of the cyclic sulfite ester include ethylene sulfite, propylene sulfite, trimethylene sulfite, butylene sulfite, and vinylene sulfite.

[0065] Examples of sultones include alkane sultones and alkene sultones. 3-5 Alcantara, C 3-5 Alkenesultones may also be used. Specific examples of sultones include 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone.

[0066] The first component also includes those having one or more substituents. The first component may have a substituent on a carbon atom constituting the ring of the first component. Examples of the substituent include an alkyl group, a hydroxyalkyl group, a hydroxy group, an alkoxy group, and a halogen atom. The number of carbon atoms in the substituent may be 1 to 4 or 1 to 3. Examples of the halogen atom include a chlorine atom and a fluorine atom.

[0067] The first component is C 2-4 Alkylene sulfate, C 2-4 Alkylene sulfite, C 3-5 Alcantara, C 3-5 Alkenesultones are preferred.

[0068] The non-aqueous electrolyte may contain one type of the first component, or may contain two or more types in combination.

[0069] The content of the first component in the non-aqueous electrolyte is, for example, 5% by mass or less, and may be 3% by mass or less. When the content of the first component is in such a range, the decrease in the non-aqueous electrolyte can be further suppressed. From the viewpoint of further enhancing the effect of suppressing the decrease in the non-aqueous electrolyte, it is preferable that the content of the first component in the non-aqueous electrolyte is 2% by mass or less. In this case, the viscosity of the non-aqueous electrolyte can be kept low and the charge / discharge reaction can proceed more uniformly, so that the consumption of the non-aqueous electrolyte is considered to be suppressed overall. In the non-aqueous electrolyte secondary battery, the content of the first component in the non-aqueous electrolyte changes during storage or charge / discharge. Therefore, it is sufficient that the first component remains in the non-aqueous electrolyte in the non-aqueous electrolyte secondary battery at a concentration equal to or higher than the detection limit. The content of the first component in the non-aqueous electrolyte may be 0.01% by mass or more.

[0070] The content of the first component in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte secondary battery may be 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more. The content of the first component in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte secondary battery may be, for example, 5% by mass or less, 3% by mass or less, or 2% by mass or less. These lower and upper limits can be combined arbitrarily. By using a nonaqueous electrolyte having a content of the first component in such a range in the manufacture of the battery, the decrease in the nonaqueous electrolyte after repeated charging and discharging can be effectively suppressed.

[0071] The content of the first component in the non-aqueous electrolyte is determined, for example, by using gas chromatography under the following conditions.

[0072] Measuring device: Shimadzu GC-2010 Plus Column: J&W HP-1 (1 μm x 60 m) Linear speed: 30.0cm / sec Inlet temperature: 270℃ Detector: FID 290℃ (sens.10 1 ) (Non-aqueous solvent) Examples of the non-aqueous solvent include cyclic carbonate esters, chain carbonate esters, cyclic carboxylate esters, and chain carboxylate esters. Examples of the cyclic carbonate esters include propylene carbonate (PC), ethylene carbonate (EC), and the like. Examples of the chain carbonate esters include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and the like. Examples of the cyclic carboxylate esters include γ-butyrolactone (GBL), γ-valerolactone (GVL), and the like. Examples of the chain carboxylate esters include methyl formate, ethyl formate, propyl formate, methyl acetate (MA), ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and the like. The non-aqueous electrolyte may contain one type of non-aqueous solvent, or may contain two or more types in combination. When the non-aqueous electrolyte contains a chain carboxylate ester, a side reaction is likely to occur when it is combined with a negative electrode mixture containing CNT. However, even in such a case, the effect of using the first component is significantly obtained. Therefore, side reactions are suppressed and high cycle characteristics can be ensured. When the nonaqueous electrolyte contains at least MA as the chain carboxylate, such an effect is more significant, which is more preferable.

[0073] (Lithium salts) The lithium salt is, for example, LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiB 10 Cl 10, lithium aliphatic carboxylates, LiCl, LiBr, LiI, borates, and imide salts. Examples of borates include lithium bis(1,2-benzenediolate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldiolate(2-)-O,O')borate, and lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate. Examples of imide salts include lithium bisfluorosulfonylimide (LiN(FSO 2 ) 2 ), lithium bistrifluoromethanesulfonimide (LiN(CF 3 SO 2 ) 2 ), lithium trifluoromethanesulfonate nonafluorobutanesulfonimide (LiN(CF 3 SO 2 )(C 4 F 9 SO 2 )), lithium bispentafluoroethanesulfonimide (LiN(C 2 F 5 SO 2 ) 2 The non-aqueous electrolyte may contain one type of lithium salt or a combination of two or more types of lithium salts.

[0074] The concentration of the lithium salt in the nonaqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less.

[0075] The non-aqueous electrolyte may contain other additives. The other additives are referred to as second components. Examples of the second component include at least one selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and vinylethylene carbonate.

[0076] (Separator) Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulating properties. For example, a microporous thin film, a woven fabric, or a nonwoven fabric, or a laminate of at least two of these materials can be used as the separator. The material of the separator is preferably polyolefin (e.g., polypropylene, polyethylene).

[0077] (others) An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.

[0078] Hereinafter, as an example of the nonaqueous electrolyte secondary battery according to the present disclosure, the structure of a prismatic nonaqueous electrolyte secondary battery will be described with reference to Fig. 1. Fig. 1 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, with a portion cut away.

[0079] The battery includes a bottomed prismatic battery case 4, and an electrode group 1 and a non-aqueous electrolyte housed within the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, positive electrode, and separator around a flat plate-shaped winding core and then removing the winding core.

[0080] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate. The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The electrolyte injection hole provided in sealing plate 5 is closed with a sealing plug 8 .

[0081] [Example] The present disclosure will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0082] Examples 1 to 6 and Comparative Examples 1 to 9 A non-aqueous electrolyte secondary battery was produced and evaluated according to the following procedure.

[0083] (1) Preparation of the negative electrode An appropriate amount of water was added to the negative electrode mixture and mixed to obtain a negative electrode slurry. The negative electrode mixture was a mixture of a negative electrode active material, a binder, and a conductive agent.

[0084] The negative electrode active material was a mixture of Si-containing material and graphite (average particle size (D50) 25 μm). The Si-containing material was Li with a conductive layer containing conductive carbon on the surface. 2y SiO 2+y Particles (y=1, average particle size (D50) 10 μm) and SiO x Particles (x=1, average particle size (D50) 5 μm) were used. Li excluding the conductive layer 2y SiO 2+y SiO excluding particles and conductive layerx The mass ratio of the particles was 1: 1. In the negative electrode active material, the mass ratio of the Si-containing material excluding the conductive layer to the graphite was 6:94.

[0085] The binders used were sodium polyacrylate (PAA-Na), sodium salt of CMC (CMC-Na), and SBR. The conductive agent used was CNT (average diameter about 1.6 nm, average length about 5 μm) containing 90 mass % or more SWCNT.

[0086] The CNT content in the negative electrode mixture was set to the value shown in Table 1. The PAA-Na, CMC-Na, and SBR contents in the negative electrode mixture were each set to 1 mass %.

[0087] Next, the negative electrode slurry was applied to the surface of the copper foil, the coating was dried, and then the copper foil was rolled to form a negative electrode mixture layer (thickness 80 μm, density 1.6 g / cm 2 ) on both sides of the copper foil. 3 ) was formed to obtain a negative electrode.

[0088] (2) Preparation of the positive electrode Lithium-containing composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O 2 To 95 parts by mass of acetylene black, 2.5 parts by mass of polyvinylidene fluoride, and an appropriate amount of NMP were added and mixed to obtain a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an aluminum foil, the coating was dried, and then rolled to form a positive electrode mixture layer (thickness 95 μm, density 3.6 g / cm) on both sides of the aluminum foil. 3 ) was formed to obtain a positive electrode.

[0089] (3) Preparation of non-aqueous electrolyte In a mixed solvent of EC, DMC, and MA (EC:DMC:MA = 20:60:20 (volume ratio)), LiPF 6 and, if necessary, the first component shown in Table 1 was dissolved to prepare a non-aqueous electrolyte. 6The concentration of the first component in the prepared non-aqueous electrolyte (initial concentration) was set to the value (mass %) shown in Table 1 as the amount of the first component added.

[0090] (4) Fabrication of non-aqueous electrolyte secondary battery An Al positive electrode lead was attached to the positive electrode obtained above, and an Ni negative electrode lead was attached to the negative electrode obtained above. In an inert gas atmosphere, the positive electrode and the negative electrode were spirally wound with a polyethylene thin film (separator) interposed therebetween to prepare a wound electrode group. The electrode group was housed in a bag-shaped exterior body formed of a laminate sheet having an Al layer, and a predetermined amount of the nonaqueous electrolyte was injected, and then the exterior body was sealed to prepare a nonaqueous electrolyte secondary battery. When the electrode group was housed in the exterior body, a part of the positive electrode lead and the negative electrode lead were each exposed to the outside from the exterior body.

[0091] (evaluation) The nonaqueous electrolyte secondary battery was subjected to a charge / discharge cycle according to the following procedure, and the remaining amount of nonaqueous electrolyte and the capacity retention rate after the cycle were determined.

[0092] In a 45°C environment, the non-aqueous electrolyte secondary battery was charged at a constant current of 0.5C (180mA) until the voltage of the battery reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05C (18mA). After a 10-minute pause, the battery was discharged at a constant current of 0.7C (252mA) until the voltage of the non-aqueous electrolyte secondary battery reached 2.5V. The discharge capacity (Ci) at this time was determined. This cycle of charging, pausing, and discharging was counted as one cycle, and 400 cycles were repeated to determine the discharge capacity (Cc) at the 400th cycle. The ratio (%) of the discharge capacity Cc to the initial discharge capacity Ci as 100% was determined as the capacity retention rate.

[0093] In addition, the non-aqueous electrolyte secondary battery after 400 cycles was disassembled to recover the remaining non-aqueous electrolyte and determine its volume. The ratio (%) of the volume of the remaining non-aqueous electrolyte to the initial volume of the non-aqueous electrolyte, which was taken as 100%, was calculated. Table 1 shows this ratio as the amount (%) of the remaining non-aqueous electrolyte.

[0094] The results of the examples and comparative examples are shown in Table 1. Table 1 also shows the CNT content (mass%) in the negative electrode mixture, and the type and amount (mass%) of the first component added to the non-aqueous electrolyte. In Table 1, E1 to E6 are examples 1 to 6, and C1 to C9 are comparative examples 1 to 9.

[0095] [Table 1]

[0096] As shown in Table 1, when the negative electrode mixture contains CNT, the remaining amount of non-aqueous electrolyte is reduced by 3.3% compared to when the negative electrode mixture does not contain CNT (comparison between C1 and C2). On the other hand, when the negative electrode mixture does not contain CNT, even if the first component is added to the non-aqueous electrolyte, the remaining amount of non-aqueous electrolyte is almost unchanged (comparison between C1 and C3 to C5). In other words, when the negative electrode mixture does not contain CNT, the first component hardly contributes to suppressing the decrease of the non-aqueous electrolyte. However, when the negative electrode mixture containing CNT is combined with the non-aqueous electrolyte containing the first component, the effect of suppressing the decrease of the non-aqueous electrolyte by the first component is exerted. Specifically, compared to C2 using a non-aqueous electrolyte not containing the first component, E1 to E6 can ensure the remaining amount of non-aqueous electrolyte that is comparable to or exceeds the amount when the negative electrode mixture does not contain CNT. Furthermore, compared to when the negative electrode mixture does not use CNT or the first component does not use, E1 to E6 can ensure a high capacity retention rate and obtain excellent cycle characteristics (comparison between C1 to C5 and E1 to E6). This is believed to be because the inclusion of CNTs in the negative electrode mixture prevents the conductive path in the negative electrode mixture from being broken when the mixture is repeatedly charged and discharged, and because the use of the first component prevents side reactions that occur when the negative electrode mixture contains CNTs, allowing electrons to be preferentially consumed in the charge and discharge reaction.

[0097] In addition, when the CNT content in the negative electrode mixture is less than 0.005 mass%, the decrease in the remaining amount of non-aqueous electrolyte due to the use of CNT is not evident (C8). Therefore, the remaining amount of non-aqueous electrolyte is almost the same as that of C8, which is a combination of a negative electrode mixture not containing CNT and a non-aqueous electrolyte containing the first component. When a negative electrode containing a CNT content of more than 0.05 mass% in the negative electrode mixture is combined with a non-aqueous electrolyte containing the first component, the effect of using the first component in suppressing the decrease in the remaining amount of non-aqueous electrolyte is not so remarkable (comparison of E2 and C2 with C7 and C9). [Industrial Applicability]

[0098] The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, etc. However, the uses of the nonaqueous electrolyte secondary battery are not limited to these. [Explanation of symbols]

[0099] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing

Claims

1. A positive electrode, a negative electrode, and a non-aqueous electrolyte, the negative electrode comprises a negative electrode mixture including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions and carbon nanotubes; the negative electrode active material includes a silicon-containing material and a carbonaceous material, the non-aqueous electrolyte contains at least one cyclic ester selected from the group consisting of a cyclic sulfate ester, a cyclic sulfite ester, and a sultone, The content of the carbon nanotubes in the negative electrode mixture is 0.005% by mass or more and 0.05% by mass or less.

2. 2 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein the negative electrode active material contains the silicon-containing material in an amount of 4 mass % or more.

3. The cyclic ester is 2-4 Alkylene sulfate, C 2-4 Alkylene sulfite, C 3-5 Alkanesultone, and C 3-5 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the electrolyte is at least one selected from the group consisting of alkenesultones.

4. 4. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of the cyclic ester in the nonaqueous electrolyte is 5 mass % or less.

5. 5. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carbon nanotubes include single-walled carbon nanotubes.

6. 6. The nonaqueous electrolyte secondary battery according to claim 5, wherein the proportion of the single-walled carbon nanotubes in the carbon nanotubes is 90% or more.

7. 7. The nonaqueous electrolyte secondary battery according to claim 1, wherein the nonaqueous electrolyte further contains a chain carboxylate ester.

8. 8. The nonaqueous electrolyte secondary battery according to claim 7, wherein the nonaqueous electrolyte contains at least methyl acetate as the chain carboxylate ester.

Citation Information

Patent Citations

  • Electrode, lithium battery, manufacturing method for electrode, and composition for electrode coating

    JP2009170410A

  • Compound electrode material

    JP2014146519A

  • Method of manufacturing electrode for battery

    JP2014160590A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries, nonaqueous electrolyte secondary battery, battery pack, and method for producing negative electrode active material for nonaqueous electrolyte secondary batteries

    WO2013145108A1